Ecossistema de inovação: a influência da qualidade de vida na retenção de talentos - Silveira, Fabiane Aparecida Tavares da (Universidade do Vale do Rio dos Sinos, 2020)
The innovation ecosystems are formed by actors capable of generating innovation, these called STEM talents, come from the areas of exact sciences, such as: engineering, mathematics, statistics and informatics. Thus, it is necessary that the ecosystem owns the capacity to retain these talents so they continue to generate innovation and promote it. However, most of the literature is focused on retaining talent in companies. In need of further advances in this type of research, especially in the issue of STEM talents. One of the ways to retain talent in an innovation ecosystem is to provide quality of life. In this sense, this research is dedicated to the following research problem: the influence of the elements that make up the quality of life for the retention of talents in the innovation ecosystem To solve this issue, 263 questionnaires with a 5-point Likert scale, survey type, were collected and questions about the quality of life were used. The data were collected in the city of Porto Alegre because it is a growing ecosystem, concerned with the retention of local talent. The results were analyzed statistically using the SPSS software, with multiple regression analysis and descriptive analysis. Conclusions: The result of this research confirms that some elements of quality of life have an influence on some aspects of the retention of STEM talents. Factors such as City Maintenance, Environmental Health and Recreational Services were identified by the Multiple Regression Analysis methods as those that have a positive relationship with talent retention (subjective aspects of quality of life), such as Neighborhood Belonging and Residential Satisfaction. Practical implications: Assist in the public policy, demonstrating that quality of life is essential for talents to wish remaining in the city and helping in the process of transformation to an innovative ecosystem as well as demonstrating to government officials what they should invest more in order for the return on education to return to the city.
Keywords: Capital social; Qualidade de vida; Retenção de talentos; Ecossistema de inovação; Quality of life; Talent retention; Innovation ecosystem; ACCNPQ::Ciências Sociais Aplicadas::Administração